A Study on Factors Influence on Purchasing Decision Special Reference to Cosmetic Products - Dr. Dayanandaswamy MS, Mrs. Shobha B H, (Design Engineering, 2021)
Change is the only constant behavior of customers. Customers preferences and choices will be depends on many factors. Understanding consumer behavior is critical to a company’s long-term success. To forecast future trends, marketing employees are continually evaluating patterns of buying behavior and purchase decisions. This study conducted with help of 385 respondents from four populated and posh areas of Bangalore city i.e. Rajajinagar, Indiranagar, Malleshwaram & Yashwanthpur for examine the demographic factors that influence on customer purchase decision of cosmetic products & made an attempt to know the elements which are influence of cosmetic purchase mode through online or in-store. The research results found that customer have great influence of age, gender & income on their buying decision of cosmetic products. Further choosing online or in-store for cosmetic shopping has their own valid reasons from each customer perspective.